Tindak Tutur Ilokusi dalam Al-Qur’an Surah Al-Baqarah Ayat 67-73 - Tamalia Rofiqoh, Noor ‘Ilma; Zaini, Hisyam (Universitas Muhammadiyah Gorontalo, 2023)
This paper will reveal the speech act in the conversation of Prophet Moses with his people, Bani Israel, which is found in the Qur'an surah Al-Baqarah verses 67 – 73. In this surah, Allah describes the conversation between the prophet Moses and his people in a form of dialogue. The dialogue between Moses and his people has diverse linguistic dimensions. On this occasion, the author examines the dialogue from the aspect of language, especially illocutionary speech acts. The data was obtained from the main source, the Qur'an surah Al-Baqarah, using documentation method followed by note-taking technique. From this study, several types of illocutionary speech acts were found, namely; (1) assertive illocutionary in the form of complaints, statements, suggestions, and notices. (2) directive illocutions in the form of sentences in the form of commands and pleadings, (3) expressive illocutions in the form of expressive statement, and (4) declarative illocutions in the form of affirmative/decisive sentences.